用于便携式电子设备的颗粒物传感器 (2023)
本主题技术方面涉及用于电子设备的颗粒物传感器。颗粒物传感器可包括三个激光器、三个全内反射透镜和三个检测器，该三个检测器用于检测三个激光器的操作由于自混合干涉测量法的原理而引起的变化。三个全内反射透镜可使用内反射表面来使三个光束倾斜成在三维空间中形成正交基的三个对应方向，以便可确定气体流速，同时保持用于在便携式电子设备中实现传感器的小型模块化形状因数。 Aspects of the subject technology relate to particulate matter sensors for electronic devices. A particulate matter sensor may include three lasers, three total-internal-reflection lenses, and three detectors for detecting changes in the operation of the three lasers due to the principles of self-mixing interferometry. The three total-internal-reflection lenses may use internally reflective surfaces to tilt the three beams into three corresponding directions that form an orthogonal basis in the three dimensional space, so that a gas flow speed can be determined while maintaining a small, modular form factor for implementation of the sensor in portable electronic devices.